2007
DOI: 10.3748/wjg.v13.i42.5612
|View full text |Cite
|
Sign up to set email alerts
|

Induction of apoptosis by artemisinin relieving the severity of inflammation in caerulein-induced acute pancreatitis

Abstract: AIM:To observe the apoptosis and oncosis of pancreatic acinar cells and secondary inflammatory reaction in pancreatic tissue from rats with acute pancreatitis (AP), and the influences of artemisinin on them. METHODS: AP was induced by 4 intraperitonealinjections of caerulein at 1 h intervals. To induce apoptosis, solution of artemisinin (50 mg/kg) was given intraperitoneally 1, 12, 24 and 36 h after the last caerulein injection. Histological examination of impairment of pancreatic tissue and detection of serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 29 publications
2
19
1
Order By: Relevance
“…In addition, apoptosis also occurs in extrapancreatic organs such as small intestine and lung, etc., and the extent of apoptosis is closely associated with the severity of multiple organ injury [26][27][28]. Some researchers believed that apoptosis was detrimental in SAP [29][30][31][32] while the others thought that apoptosis might provide some protective effects in SAP process [18,20,33,34]. The results of this study support the latter view.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In addition, apoptosis also occurs in extrapancreatic organs such as small intestine and lung, etc., and the extent of apoptosis is closely associated with the severity of multiple organ injury [26][27][28]. Some researchers believed that apoptosis was detrimental in SAP [29][30][31][32] while the others thought that apoptosis might provide some protective effects in SAP process [18,20,33,34]. The results of this study support the latter view.…”
Section: Discussionsupporting
confidence: 87%
“…One of the important cytotoxic mechanisms of oxygen free radicals, which were excessively generated in SAP, was to induce apoptosis [38][39][40]. Chen HM et al [30] found that neutrophils apoptosis were beneficial to SAP patients. In SAP, the number of apoptotic neutrophils decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, we determined expression of markers of necrotic (MMP9) and apoptotic (active form of caspases 8, 9, and 3) cell death in control versus sEHI-treated mice prior and post-AP induction. In line with published reports (Frossard et al, 2003;Zhao et al, 2007), cerulein treatment led to significant increase in MMP9, caspase 3 expression, as well as caspases 8 and 9 (Fig. 5A).…”
Section: Resultssupporting
confidence: 80%
“…The substantial difference between apoptosis and necrosis depends on causing intense inflammatory reaction or not. According to some studies, when necrosis and apoptosis coexist and necrosis prevails, inducing apoptosis will result in protective effects on related organs [13,[19][20][21]. We have found that facilitating thymus apoptosis has active protecting effects on thymus by comparing the apoptotic indexes and pathological score.…”
Section: Discussionmentioning
confidence: 91%